2017
DOI: 10.1017/s0031182017000658
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansonicercarial elastase (SmCE): differences in immunogenic properties of native and recombinant forms

Abstract: The Schistosoma mansoni cercarial elastase (SmCE) has previously been shown to be poorly immunogenic in mice. However, a minority of mice were able to produce antibodies against SmCE after multiple immunizations with crude preparations containing the enzyme. These mice were partially protected against challenge infections of S. mansoni. In the present study, we show that in contrast to the poor immunogenicity of the enzymatically active native form of SmCE derived from a crude preparation (cercarial transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Elastases are the trypsin-like proteins belonging to the family of serine proteases, they can degrade host's various macromolecular substances such as keratin, laminin, type IV collagen, fibronectin and elastin [64]. The elastases are involved in larva invasion, molting and digestion, and may exert a major action for parasite invasion [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Elastases are the trypsin-like proteins belonging to the family of serine proteases, they can degrade host's various macromolecular substances such as keratin, laminin, type IV collagen, fibronectin and elastin [64]. The elastases are involved in larva invasion, molting and digestion, and may exert a major action for parasite invasion [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Elastase is a trypsin-like serine protease that can hydrolyze the host's diverse tissue components (e.g., fibronectin, laminin, type IV collagen, elastin). The elastases participate in parasite penetration, molting and digestion and may play a major role in worm intrusion of hosts [62]. In our previous study, TsE was cloned, expressed and identified, and it was likely a novel target molecule for preventive vaccines against T. spiralis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Elastases belong to a trypsin-like serine protease which has the ability to hydrolyse various tissue components, such as fibronectin, laminin, collagen and elastin. The elastases are involved in the parasite invasion and digestion, and might a crucial role act in worm invasion (El-Faham et al 2017). In a previous study, the TsE was cloned and expressed in Escherichia coli, and the rTsE might be a novel target molecule for anti-T. spiralis vaccines (Hu et al 2020).…”
Section: Discussionmentioning
confidence: 99%